Growth and NPK level of two rice varieties (oryza sativa L.) due to differences in the combination of inorganic and biological fertilization - Mazidatul Faizah; Mohamad Nasirudin (Agrovigor, 2025)
The increase on rice plant growth can be done through the application of organic and inorganic fertilizers, as well as the use of appropriate varieties. This research aimed to examine the effect of a combination of organic and inorganic fertilizer doses and the use of varieties on improving rice plant growth and nutrient level. The research was conducted from June to August 2025 located in Sudimoro Village, Megaluh Subdistrict, Jombang Regency. This research used a factorial randomized block design (RBD) with two factors and three replications. Factor 1 is a combination of biological and inorganic fertilizer doses consisting of 9 levels of treatment, namely: 100% inorganic fertilizer + no biological fertilizer (P1), 75% inorganic fertilizer + no biological fertilizer (P2), 50% inorganic fertilizer + no biological fertilizer (P3), 100% inorganic fertilizer + 5 ml biological fertilizer (P4), 75% inorganic fertilizer + 5 ml biological fertilizer (P5), 50% inorganic fertilizer + 5 ml biological fertilizer (P6), 100% inorganic fertilizer + 10 ml biological fertilizer (P7), 75% inorganic fertilizer + 10 ml biological fertilizer (P8), and 50% inorganic fertilizer + 10 ml biological fertilizer (P9). Factor 2 is the rice plant varieties, namely: Inpari 32 (V1) and Ciherang (V2). The observations conducted included growth observations, namely plant height, number of leaves, number of tillers and dry weight of plants observed at 15, 30, 45, and 60 days after planting and NPK level of plants observed at 60 days after planting. The results showed that the combination of 100% inorganic fertilization + 10 ml of organic fertilizer generally increased plant height, number of leaves and dry weight of rice plants. The use of the Ciherang variety resulted in better plant height, number of leaves and dry weight of rice plants compared to the Inpari 32 variety. The use of a combination of inorganic and organic fertilizer had a significant effect on increasing the number of tillers of rice plants of the Inpari 32 variety compared to the Ciherang variety. The nitrogen content of rice plants (1.17 to 1.99%) is included in the deficiency category, while the phosphorus content (0.14 to 0.31%) and potassium (1.45 to 2.22%) are included in the excess category, where the addition of biofertilizer has an effect on increasing the nitrogen, phosphorus and potassium content of rice plants compared to without biofertilizer.